Translocational Positionality of Returnee Migrants: The New Normal - Dzintra Iliško; Jelena Badjanova; Michal Šimáně (Language, Culture, Politics)
The globalization and migration processes are typical features of our societies that affect policy, economy and the culture of each country. Migration involves many challenges: identity issues and well-being of migrants in negotiating new roles and values. At the social level, migration involves demographic, educational, sociological and employment aspects. The reasons of migration are numerous, including the economic as the major one. The authors employ a multidisciplinary approach by drawing on the geographical, sociological and anthropological disciplines in disclosing the narrative of returnees. The methodology employed in this study is based on semi structured interviews with seven returnee women. The study focuses on the transcultural and transnational positionality of the Latvian returnee migrants who are trying to settle down in Latvia, by revealing their hopes and struggles while relocating in a new cultural context. In this study, the authors place a particular focus on the narratives of female returnees. The main question is directed at how the returnees locate themselves at the conjuncture of diverse localities in building their transcultural identity.